THE PLACE AND SIGNIFICANCE OF COMPLEX PARTICLES IN THE SENTENCE (On the example of the works of Azod Sharafiddinov) (Scientific journal of the Fergana State University, 2025)
Today, in the field of linguistics, many scientific studies are conducted to determine the phonological, lexical and semantic layers of the language, as well as the semantics of syntactic units. There are different approaches to the theory of analysis at the syntactic level, which is important in world linguistics. Therefore, in this article, we will also discuss the possibilities of singular connectives, the expressive possibilities of repetitive connectives in the works of the skilled wordsmith, critic Ozod Sharafiddinov, used in cohesive clauses, in creating a text typical of the scientific style, and, we have tried to syntactically analyze issues such as how it uses conjunctions without conjunctions and subtractive conjunctions.